Optimizing Age Estimation in Facial Images with Advanced Multi-Class Classification Techniques - R., Karthickmanoj; S.Aasha, Nandhini; D., Lakshmi; R., Rajasree (INTI International University, 2024)
Automatic age and gender prediction from facial images is increasingly crucial for applications in security, marketing, and social media. Existing systems often face challenges related to accuracy, demographic generalization, and bias. This study addresses these issues by developing a deep learning-based system utilizing Convolutional Neural Networks (CNNs) for enhanced classification of age and gender. The key research gaps include limited accuracy, insufficient handling of diverse data, and model bias. The proposed approach encompasses data acquisition, preprocessing, and the design of a CNN architecture within a multi-class classification framework. Various CNN models are evaluated, incorporating transfer learning, hyperparameter optimization, and regularization techniques to improve performance. The system's effectiveness is assessed through metrics such as classification accuracy, precision, recall, and robustness across different demographic groups. Results indicate significant advancements in prediction accuracy and model generalization compared to existing methods. The technology holds practical applications in security, personalized marketing, and social networking. Challenges such as model bias and the need for diverse datasets are addressed, with future research aimed at further refining the model and expanding its applicability. This work highlights the substantial improvements deep learning offers to facial recognition technologies.